2008
DOI: 10.1152/ajpregu.00091.2008
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic translation control in the late-gestation fetal rat

Abstract: We have investigated the regulation of translation during the period of rapid liver growth that occurs at the end of gestation in the rat. This work was based on our prior observation that fetal hepatocyte proliferation is resistant to the inhibitory effects of rapamycin, an inhibitor of the mammalian target of rapamycin (mTOR), a nutrient-sensing kinase that controls ribosome biogenesis and protein translation. We hypothesized that translation control in late-gestation fetal liver differs from that in adult l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
0
13
1
Order By: Relevance
“…Profiling of the fetal translatome in our present studies did not disclose an IUGR-associated effect on 5=TOP translation. Our previous studies on mechanisms of hepatic translation control in the late-gestation fetal rat (28) showed marked fetal-adult differences in the composition of the cap-binding translation initiation complex. These included the identification of isoforms of the cap-binding complex scaffolding protein, eIF4G, that were specific to fetal liver and fetal-adult isoform differences in the eIF4A helicase.…”
Section: Discussionmentioning
confidence: 93%
“…Profiling of the fetal translatome in our present studies did not disclose an IUGR-associated effect on 5=TOP translation. Our previous studies on mechanisms of hepatic translation control in the late-gestation fetal rat (28) showed marked fetal-adult differences in the composition of the cap-binding translation initiation complex. These included the identification of isoforms of the cap-binding complex scaffolding protein, eIF4G, that were specific to fetal liver and fetal-adult isoform differences in the eIF4A helicase.…”
Section: Discussionmentioning
confidence: 93%
“…RNA was further purified using the RNeasy Mini Kit (Qiagen, Valencia, CA). Translating polysomes were prepared and isolated by sucrose density centrifugation (14). RNA was extracted from pooled polysome preparations by acid-phenol:chloroform extraction followed by precipitation in ethanol plus ammonium acetate.…”
Section: Methodsmentioning
confidence: 99%
“…Several years ago, we made the observation that late gestation fetal hepatocytes in vivo were resistant to the growth inhibitory effects of rapamycin (5). We went on to examine the hepatic translation control apparatus in the late gestation fetus (14). The results of our studies indicated resistance to the growth inhibitory effect of rapamycin at the level of G1 cell-cycle progression (13) and translation of 5=TOP mRNAs (12,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis was tested using the model of direct administration of rapamycin to late gestation (ED19) fetal rats in situ. 32 We first examined the ability of rapamycin to inhibit the translation of mRNAs encoding ribosomal proteins; that is, those mRNAs containing 5'-terminal oligopyrimidine (5'TOP) tracts. As expected, the activation of hepatic translation of 5'TOP mRNAs that occurred during refeeding after food deprivation was sensitive to rapamycin.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%